Low-Grade Uterine Endometrial Stromal Sarcoma: Prognostic Analysis of Clinico-Pathological Characteristics, Surgical Management, and Adjuvant Treatments. Experience From Two Referral Centers - Borella, Fulvio; Bertero, Luca; Cassoni, Paola; Piovano, Elisa; Gallio, Niccolò; Preti, Mario; Cosma, Stefano; Ferraioli, Domenico; Pace, Luca; Mariani, Luca; Biglia, Nicoletta; Benedetto, Chiara (Frontiers in Oncology, 2022)
Objective Low-grade uterine endometrial stromal sarcoma (LG-ESS) is a rare tumor characterized by an overall good survival but showing a indolent behavior and a variable risk of recurrence. There is no clear consensus on the optimal management of these tumors and no prognostic or predictive factors have been established. With this study, we evaluated the prognostic relevance of several clinical, surgical, and pathological features in patients affected by LG-ESS to identify risk factors associated with recurrence. Methods We retrospectively analyzed 52 LG-ESS cases, treated from January 1st, 1994, to May 31st, 2020, in two referral centers. The relationship between recurrence and clinicopathological characteristics as well as surgical treatment was investigated. Risk of recurrence and disease-free survival (DFS) were estimated by Cox regression and the Kaplan-Meier analysis, respectively. Results Of 52 patients with LG-ESS, 8 experienced recurrence (15%). The median follow-up was 100 months (SD ± 96, range: 15–336). By univariate analysis, fragmentation/morcellation, tumor size, FIGO stage, higher mitotic count, presence of necrosis, and lymphovascular space invasion (LSVI) resulted associated with a poorer outcome. Conversely, the surgical modality (laparotomic vs laparoscopic and hysterectomy with bilateral salpingo-oophorectomy vs local excision) and pelvic lymphadenectomy were not. Even the different modalities of adjuvant therapy (hormonal therapy, radiotherapy, and chemotherapy) showed no prognostic significance. Tumor fragmentation/morcellation and higher mitotic count resulted independent prognostic variables at multivariate analysis. Conclusions This data supports the avoidance of any type of morcellation if LG-ESS is suspected preoperatively. Higher mitotic count and, possibly, tumor size, advanced FIGO stage, necrosis, and LVSI could be exploited to tailor the adjuvant therapy, but these results need to be confirmed in larger prospective studies.